Instilling moral values in report writing course - Abu Samah, Siti Akmar; Jusoff, Kamaruzaman (Canadian Center of Science and Education, 2008)
This topic may raise eyebrows of its relevance, significance and approaches. Very often than not several soft skills initiatives have been put forward by the top leaders of the country, of which are very commonly known as, for example, Rukun Negara, Pelan Integriti Negara (PIN) , and the recent one – Kemahiran Insaniah. All these are targeted to the working population of the country. However, these are noble values that need to be instilled at much tender age of our youths. Being teachers at tertiary level, do we play a part in this work of nurturing the nature. If we are not obligated to, is our teaching merely facts dissemination and completing the syllabus? If we have the sense of responsibility being citizens with these noble values, do we impart them to our students? And just how do we do that? In a small area of focus, teaching Report Writing entails much trust in the choice of topic, data collection, researching for literature, drafting and writing. These are the tasks that need to be carried out by the students. They are the process owner of their project and in conducting so, the trustworthiness sometimes may swerve to plagiarized work, cut-paste practice or copying from others in carrying out their assignment. Can we inculcate values in every juncture of progress that they make? This paper attempts to address so by providing pertinent teaching-learning strategies.